Optical vortices and the flow of their angular momentum in a multimode fiber - Alexeyev, A.N.; Fadeyeva, T.A.; Volyar, A.V.; Soskin, M.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
The problem of propagation of optical vortices in multimode fibers is considered. The structural changes experienced by the wave and ray surfaces in their transformation from the free space to a fiber medium are determined. The continuity equation is obtained for the flow of the vortex angular momentum in an unhomogeneous medium. Розглядається проблема розповсюдження оптичних вихорів в багатомодових волокнах. Показано які структирнихзмін дізнають хвильова і променева поверхні при переході із вільного простору в середовище волокна. Записане рівняння неперервності для потоку кутового момента вихоря в неоднорідному середовищі. Рассматривается проблема распространения оптических вихрей в многомодовых волокнах. Показано какие структурные изменения испытывают волновая и лучевая поверхности при переходе из свободного пространства в среду волокна. Записано уравнение непрерывности для потока углового момента вихря в неоднородной среде.